Inventory of the Genus Bougainvillea (Nyctaginaceae) at Bukit Bougenville Agrotourism Park, Singkawang, West Kalimantan - Nambisas Arum Kusuma Ayu; Widya Astuti; Isyatirradhiyah Isyatirradhiyah; Mas Akhbar Faturrahman; Hayatul Fajri (Jurnal Pijar MIPA, 2026)
The high level of biodiversity Indonesia contains is a prestigious national treasure. One type of biodiversity found in Indonesia is plant diversity. Plant diversity is inevitable due to their use as ornamental plants. Among many ornamental plants famous in Indonesia, the genus Bougainvillea Comm. ex Juss is known globally for its essential role in horticulture development. Bukit Bougenville Agrotourism Park, located in Sijangkung Subdistrict, South Singkawang District, Singkawang City, West Kalimantan Province, maintains a diverse and abundant collection of cultivated Bougainvillea plants, which can serve as an important resource for investigating Bougainvillea diversity. To date, no research has inventoried the diversity of Bougainvillea in Bukit Bougenville Agrotourism Park. Therefore, this research aims to inventory and identify members of the Bougainvillea genus found in Bukit Bougenville Agrotourism Park. Using a qualitative method, this research involved the Bougainvillea members at the research site, sampled using convenience sampling due to the vast area. The research is then continued with identification based on morphology, supported by various peer-reviewed literature. The identification process revealed two species: Bougainvillea spectabilis Willd., both in non-variegated and variegated forms, and Bougainvillea glabra Choisy. The sampling also revealed substantial numbers of each species in Bukit Bougenville Agrotourism Park: B. spectabilis in non-variegated form, totalling 237 individuals; B. spectabilis in variegated form, totalling 126 individuals; and B. glabra, totalling 53 individuals, for a total of 416 individuals encountered throughout the sampling period. The identification and abundance of the two species indicate that the area has favorable ecological conditions for cultivating Bougainvillea, supporting its role as a specialized agrotourism destination. Overall, the results provide a baseline inventory for future planning regarding conservation, landscape management, and ornamental plant breeding programs. Moreover, the documented species composition can inform agrotourism development strategies, including educational interpretation, biodiversity-based tourism promotion, and sustainable plant management practices.